Feather corticosterone reveals stress associated with dietary changes in a breeding seabird. Issue 19 (7th September 2015) - Will, Alexis; Watanuki, Yutaka; Kikuchi, Dale M.; Sato, Nobuhiko; Ito, Motohiro; Callahan, Matt; Wynne‐Edwards, Katherine; Hatch, Scott; Elliott, Kyle; Slater, Leslie; Takahashi, Akinori; Kitaysky, Alexander
Abstract Changes in climate and anthropogenic pressures might affect the composition and abundance of forage fish in the world's oceans. The junk‐food hypothesis posits that dietary shifts that affect the quality (e.g., energy content) of food available to marine predators may impact their physiological state and consequently affect their fitness. Previously, we experimentally validated that deposition of the adrenocortical hormone, corticosterone, in feathers is a sensitive measure of nutritional stress in seabirds. Here, we use this method to examine how changes in diet composition and prey quality affect the nutritional status of free‐living rhinoceros auklets (Cerorhinca monocerata). Our study sites included the following: Teuri Is. Japan, Middleton Is. central Gulf of Alaska, and St. Lazaria Is. Southeast Alaska. In 2012 and 2013, we collected "bill loads" delivered by parents to feed their chicks (n = 758) to document dietary changes. We deployed time–depth–temperature recorders on breeding adults (n = 47) to evaluate whether changes in prey coincided with changes in foraging behavior. We measured concentrations of corticosterone in fledgling (n = 71) and adult breeders' (n = 82) feathers to determine how birds were affected by foraging conditions. We found that seasonal changes in diet composition occurred on each colony, adults dove deeper and engaged in longer foraging bouts when capturing larger prey and that chicks had higher concentrations of corticosterone in their feathers when adults brought back smaller and/or lower energy prey. Corticosterone levels in feathers of fledglings (grown during the breeding season) and those in feathers of adult breeders (grown during the postbreeding season) were positively correlated, indicating possible carryover effects. These results suggest that seabirds might experience increased levels of nutritional stress associated with moderate dietary changes and that physiological responses to changes in prey composition should be considered when evaluating the effect of prey quality on marine predators.